Effect of Antibiotic-Mediated Microbiome Modulation on Rotavirus Vaccine Immunogenicity: A Human, Randomized-Control Proof-of-Concept Trial - Harris, Vanessa C.; Haak, Bastiaan W.; Handley, Scott A.; Jiang, Baoming; Velasquez, Daniel E.; Hykes, Barry L.; Droit, Lindsay; Berbers, Guy A.M.; Kemper, Elles Marleen; van Leeuwen, Ester M.M.; Boele van Hensbroek, Michael; Wiersinga, Willem Joost (Cell host & microbe, 2018)
Rotavirus vaccines (RVV) protect against childhood gastroenteritis caused by rotavirus (RV) but have decreased effectiveness in low- and middle-income settings. This proof-of-concept, randomized-controlled, open-label trial tested if microbiome modulation can improve RVV immunogenicity. Healthy adults were randomized and administered broad-spectrum (oral vancomycin, ciprofloxacin, metronidazole), narrow-spectrum (vancomycin), or no antibiotics and then vaccinated with RVV, 21 per group per protocol. Baseline anti-RV IgA was high in all subjects. Although antibiotics did not alter absolute anti-RV IgA titers, RVV immunogenicity was boosted at 7 days in the narrow-spectrum group. Further, antibiotics increased fecal shedding of RV while also rapidly altering gut bacterial beta diversity. Beta diversity associated with RVV immunogenicity boosting at day 7 and specific bacterial taxa that distinguish RVV boosters and RV shedders were identified. Despite the negative primary endpoint, this study demonstrates that microbiota modification alters the immune response to RVV and supports further exploration of microbiome manipulation to improve RVV immunogenicity. [Display omitted] •Rotavirus vaccine immunogenicity tested following antibiotic administration in adults•Antibiotics did not alter absolute anti-RV IgA titers•Narrow-spectrum antibiotics increased anti-RV IgA boosting and RV shedding by day 7•Microbiome composition correlates with RVV boosting and shedding Rotavirus vaccines (RVV) are less effective in poor-resourced settings. This randomized-controlled trial in adults tested the effect of microbiome modulation via broad-spectrum, narrow-spectrum, or no antibiotics on RVV performance. Absolute anti-RV IgA titer did not change. However, antibiotics resulted in higher day-7 boosting and increased RV-antigen shedding.